Effect of dexmedetomidine on postoperative sleep quality and complications in women undergoing elective cesarean delivery - YOU Yiying, ZHONG Weilong, WANG Yanling, LI Liping (Xin yixue)
Objective To evaluate the effect of dexmedetomidine on postoperative sleep quality and complications in women undergoing elective cesarean delivery. Methods 180 women undergoing elective cesarean delivery were selected and randomly divided into the dexmedetomidine group （group D） and control group （group C）， 90 cases in each group. Dexmedetomidine 0.5 μg/kg（group D） or 10 mL of 0.9% sodium chloride injection was pumped within 15 min after fetal extraction. Maternal sleep status was assessed by Pittsburgh Sleep Quality Index （PSQI） and Insomnia Severity Index （ISI） for 24 h， 48 h postoperatively and 1 day before discharge. Maternal resting pain and activity-induced pain at 24 h and 48 h postoperatively were recorded by visual analog score （VAS） in both groups. Other perioperative complications of labor were recorded. Results The PSQI scores and ISI scores of the women in group D were lower than those of the women in group C at 24 h， 48 h after surgery and 1 day before discharge （all P < 0.05）. The incidence of severe sleep disorders and insomnia at 24 h postoperatively was lower in group D than that in group C （P = 0.031 and P =0.021）. The women in group D had less resting pain and activity-induced pain at 24 h and 48 h postoperatively， and the number of postoperative PCEA compressions was also lower （all P < 0.05）. The incidence of postoperative nausea and vomiting， itchy skin complications was lower in group D. The time to first postoperative activity， the length of postoperative hospital stay was shorter， degree of satisfaction during hospitalization was higher， and the incidence of depression at 6 weeks postpartum was also lower （all P < 0.05）. Conclusion Dexmedetomidine improves sleep quality after cesarean delivery， reduces postoperative pain and complications.